2021
DOI: 10.3389/fmolb.2021.669366
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Hsp70 and Activated NK Cells for Prediction of Prognosis in Glioblastoma Patients

Abstract: Despite rapid progress in the treatment of many cancers, glioblastoma remains a devastating disease with dismal prognosis. The aim of this study was to identify chaperone- and immune-related biomarkers to improve prediction of outcome in glioblastoma. Depending on its intra- or extracellular localization the major stress-inducible heat shock protein 70 (Hsp70) fulfills different tasks. In the cytosol Hsp70 interferes with pro-apoptotic signaling pathways and thereby protects tumor cells from programmed cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
(78 reference statements)
0
10
1
Order By: Relevance
“…The chaperone Hsp70 have been found increased or decreased in human cancers by comparison with healthy control tissues [43][44][45]. An inverse correlation between Hsp70 levels and prognosis has been observed in some cancers [35,46]. In contrast to these findings, we did not detect a clear positivity reaction for Hsp70 in the GBM tissues we describe here, although we found low but still detectable levels of this chaperone in the commercially available stem line G166.…”
Section: Discussioncontrasting
confidence: 85%
“…The chaperone Hsp70 have been found increased or decreased in human cancers by comparison with healthy control tissues [43][44][45]. An inverse correlation between Hsp70 levels and prognosis has been observed in some cancers [35,46]. In contrast to these findings, we did not detect a clear positivity reaction for Hsp70 in the GBM tissues we describe here, although we found low but still detectable levels of this chaperone in the commercially available stem line G166.…”
Section: Discussioncontrasting
confidence: 85%
“…The enigmatic and sophisticated association linking immunity with mitophagy are being gradually uncovered with the progress of the experimental research. One study from Paul K revealed that mitophagy could trigger the proliferation of CD8 + cell to improve prognosis in cancer [ 45 ]. Another study from Alejandro López-Soto suggested that the function of NK cell can be modulated by mitophagy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enigmatic and sophisticated association linking immunity with mitophagy are being gradually uncovered with the progress of the experimental research. One study from Paul K reveal that mitophagy trigger the proliferation of CD8 + cell to improve prognosis in cancer [45]. Another study from Alejandro López-Soto suggested that the function of NK cell can be modulated by mitophagy [46].…”
Section: Discussionmentioning
confidence: 99%